Fibre-optic salinity sensor based on multimode fibre specklegram analysis. (20th July 2021) - Lin, Wei; Liu, Bo; Liu, Haifeng; Yang, Chengkun; Zhang, Hao
Abstract: In this work, we propose a real-time salinity sensor based on fibre specklegram analysis. The sensor head is simply composed of a stripped multimode fibre (MMF). The laser specklegram formed at the output of the MMF is exploited for the measurement of water salinity. As water salinity varies, the refractive index (RI) would alter accordingly, resulting in the change of the laser specklegram. A RI sensitivity of −6.819/RIU, corresponding to a salinity sensitivity of −0.01086/% for the salinity range of 10%–20% has been experimentally achieved. Compared with traditional salinity sensors, the proposed sensor benefits from cost-effective, simplicity, easy of fabrication and reproductivity, which makes it a good candidate for applications in environmental monitoring and marine science.